COULOMB STRESS CHANGES DUE TO RECENT ACEH EARTHQUAKES - Madlazim, M (Universitas Negeri Surabaya, 2015)
Coulomb stress change analysis has been applied to understand whether the 2013/07/02 (Mw=6.1) has been triggered by 2013/01/21 earthquake (Mw=6.1) the proximity to failure on the Aceh segment of Sumatra Fault Zone (SFZ). We examine the problem of how one earthquake might trigger another using Coulomb stress changes plotting. To plot the Coulomb stress changes, we used Global CMT data for the both earthquakes and used GEOFON data for manually revised epicenters of its aftershocks. The earthquakes are located on Aceh segment of the historic no recorded large earthquake. Coulomb stress changes modeling of the both earthquakes and plot their aftershocks. Surprisingly, the 2013/07/02 earthquake is located on increasing Coulomb stress changes region of 2013/01/21 earthquake plotting. Here explain that the 2013/07/02 earthquake has been triggered by the 2013/01/21 earthquake. Further, the two aftershocks of the 2013/07/02 earthquake is located on increasing Coulomb stress changes region of 2013/07/02 earthquake plotting. So that, the aftershocks has been triggered by increasing Coulomb stress changes of the 2013/07/02 earthquake.